2013
DOI: 10.3109/1040841x.2013.763219
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between essential oil components and antibiotics: a review

Abstract: With the increase in antibiotic-resistant bacteria and the lack of new antibiotics being brought onto the market, alternative strategies need to be found to cope with infections resulting from drug-resistant bacteria. A possible solution may be to combine existing antibiotics with phytochemicals to enhance the efficacy of antibiotics. A group of phytochemicals that is said to have such effects, according to in vitro studies, is essential oils (EOs) and their components. Amongst others, EOs containing carvacrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
350
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(365 citation statements)
references
References 95 publications
4
350
0
11
Order By: Relevance
“…Essential oils containing carvacrol, cinnamaldehyde, cinnamic acid, eugenol and thymol can have a synergistic effect in combination with other antibacterial agents (Langeveld et al, 2014;Bassolé and Juliani, 2012). The present study showed that the antibacterial activity against the S. aureus in the film incorporated with CEO + PPE was significantly higher than that incorporated with CEO or PPE alone, suggesting there is a synergistic action between CEO and PPE.…”
Section: Mechanical Propertiessupporting
confidence: 46%
“…Essential oils containing carvacrol, cinnamaldehyde, cinnamic acid, eugenol and thymol can have a synergistic effect in combination with other antibacterial agents (Langeveld et al, 2014;Bassolé and Juliani, 2012). The present study showed that the antibacterial activity against the S. aureus in the film incorporated with CEO + PPE was significantly higher than that incorporated with CEO or PPE alone, suggesting there is a synergistic action between CEO and PPE.…”
Section: Mechanical Propertiessupporting
confidence: 46%
“…Broth micro dilution checkerboard method was used to determine the potential synergistic interactions between Mentha pulegium essential oil and antibiotics on 96 well-plate [14,15]. Nine conventional antibiotics have been used (table 4).…”
Section: Synergistic Interaction Between Mentha Pulegium Essential Oimentioning
confidence: 99%
“…(Lauraceae) is an efficacious remedy for the treatment of gastritis in traditional Iranian folk medicine (Arzani, 2005). Cinnamomum verum contains mainly cinnamaldehyde (61.57%) which is an aromatic aldehyde with an antimicrobial (Langeveld et al, 2014;Visvalingam et al, 2013) and antiviral activity (Ding et al, 2010). Cinnamaldehyde inhibited the growth of all the 30 H. pylori strains tested, at a concentration of 2 mg/mL, in the 12th h of incubation.…”
Section: Cinnamomum Verum (C Zeylanicum)mentioning
confidence: 99%